A low resistance temperature coefficient resistor paste for printed circuits of electrical components

By using high-temperature solid phase reaction of alloy powder such as tungsten powder and specific inorganic non-metal powder in metal cermet heater, the problem of excessive resistance temperature coefficient of the existing tungsten slurry is solved, and the effect of rapid heating of the device and high heating power at high temperature is achieved.

CN119170324BActive Publication Date: 2025-02-28YIXING MEI SHENG MICROELECTRONICS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411685762.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2025-02-28
Estimated Expiration
2044-11-23

AI Technical Summary

Technical Problem

The resistance temperature coefficient of existing tungsten slurry is large, which causes the device to change greatly at room temperature and operating temperature, the temperature rises slowly, and the power decreases at high temperatures, which cannot meet the heating requirements of the rapidly heating cermet heater.

Method used

The alloy powder formed by high-temperature solid phase reaction of tungsten powder, molybdenum powder, tantalum powder, niobium powder, and manganese powder are used as the conductive phase, and chromium trioxide powder and titanium dioxide powder are added to the inorganic non-metal powder. Combined with a specific organic carrier formula, a low resistance temperature coefficient resistance slurry for electrical component printing circuits is prepared.

Benefits of technology

The temperature coefficient of the resistive slurry is effectively reduced to (0.05~0.1)×10-3/℃, the heating speed of the device and the heating power at high temperatures are improved, the adhesion between the resistive film and the substrate is enhanced, and the thermal shock resistance and resolution are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a low resistance temperature coefficient resistor paste for printed circuits of electrical components, which is composed of conductive phase powder, inorganic non-metallic powder, and organic carrier. The conductive phase powder is an alloy prepared by a high-temperature solid phase method of tungsten powder, molybdenum powder, tantalum powder, niobium powder, and manganese powder. The inorganic non-metallic powder is prepared by high-temperature roasting of calcium silicate, magnesium oxide, lanthanum oxide, chromium oxide, titanium dioxide, and nano-silicon dioxide in an air atmosphere. The paste of the present invention is stable and will not precipitate after being stored for 6 months at room temperature. The paste has good thixotropy, is easy to print, does not stick to the screen, and has high resolution. The electrical component prepared by the paste of the present invention has a small resistance temperature coefficient (TCR= (0.05-0.1)×10 ‑3 / ℃), fast heating; electrical components have high power at high temperatures and are energy-saving; the thermal expansion coefficients of the slurry match those of the ceramic substrate, and the electrical components have good thermal shock resistance; the slurry forms a strong bond with the ceramic substrate through the glass phase and chemical bonds, with good adhesion and high reliability of the electrical components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic materials for electrical components, and in particular relates to a low resistance temperature coefficient resistor paste for electrical component printed circuits. Background Art

[0002] Metal ceramic heaters are made of high temperature resistant electronic pastes such as tungsten paste, molybdenum manganese paste, etc., printed on ceramic green tapes such as alumina, aluminum nitride, beryllium oxide, silicon nitride, etc., and then formed into heating elements through lamination, hot isostatic pressing, cutting, and high temperature co-firing. Electrical components manufactured using the co-firing process have the characteristics of long life, high temperature resistance, high reliability, good consistency, compact structure, small size, light weight, etc., and have become the preferred way of electronic component integration and modularization with their excellent electronic, mechanical, and thermal properties, and have been widely used in military, aerospace, computer, industry, life and other fields.

[0003] Metal ceramic heaters use high temperature resistant ceramic substrates and conductive materials, which are highly temperature resistant and very suitable for high-power devices. The devices can work at 500-1000℃ for a long time. The technology of co-firing tungsten slurry, molybdenum manganese slurry and ceramic green tape is used to prepare a wide variety of devices, which are widely used in various fields of military and civilian. Such as metal ceramic hair straighteners, heating components in nucleic acid detection instruments, base packaging of high-power crystal triodes, electronic cigarette atomizers, high-voltage discharge ceramic ozone sheets, oven igniters, high thermal conductivity ceramic shells for large-scale integrated circuits, heating components of automobile exhaust detection sensors, electric soldering irons, instant electric water heaters, ceramic heating sheets in thermal cutting and medical heating fields, heating rods for automatic flushing toilets, etc. Due to the use of high temperature co-firing technology, the circuit is wrapped in ceramics, does not come into contact with air, and has stable conductivity; at the same time, the conductive slurry matches the thermal expansion coefficient of ceramics, and has good thermal shock resistance.

[0004] In the existing preparation technology of tungsten paste, there are few patents related to the resistance temperature coefficient of tungsten paste. As a power device, the resistance temperature coefficient is extremely important. The resistance temperature coefficient of pure tungsten paste is relatively large, basically ≥5×10 -3 / ℃, resulting in a large change in the resistance of the device made of tungsten slurry at room temperature and working temperature. As a result, the device heats up slowly and the power is significantly reduced at high temperature. In the invention patent application with publication number CN109734480A and invention name "A co-fired high-temperature slurry for AlN ceramic heater and its preparation method", a tungsten slurry formula for AlN substrate was announced. The prepared slurry has a square resistance of 3.0~30.0Ω / □, and 0.67~0.74 parts of rhenium powder are used. The resistance temperature coefficient of the prepared tungsten slurry is (1.0~4.0)×10 -3 / ℃, the resistance temperature coefficient is still too large in use. In the invention patent with announcement number CN112289483B and invention name "A tungsten paste for high-power circuits", the tungsten paste formula for high-power circuits was announced. The resistance temperature coefficient of the prepared tungsten paste is TCR = (0.2~1)×10 -3 / ℃, the resistance temperature coefficient of the tungsten slurry prepared by this patent is still relatively large and cannot meet the heating requirements of the metal ceramic heater with rapid heating. Summary of the invention

[0005] The object of the present invention is to provide a low resistance temperature coefficient resistor paste for electrical component printed circuits which has low resistance temperature coefficient, fast temperature rise and high heat generation power at high temperature.

[0006] To achieve the above-mentioned purpose, the low resistance temperature coefficient resistor paste for printed circuits of electrical components used in the present invention is composed of the following raw materials in mass percentage: 70% to 80% conductive phase powder, 5% to 15% inorganic non-metallic powder, and 10% to 15% organic carrier; wherein the conductive phase powder is an alloy powder prepared by a high-temperature solid phase method from the following raw materials in mass percentage: 30% to 40% tungsten powder, 40% to 60% molybdenum powder, 4% to 16% tantalum powder, 1% to 3% niobium powder, and 1% to 2% manganese powder; the inorganic non-metallic powder is prepared by calcining the following raw materials in mass percentage in an air atmosphere: 50% to 60% calcium silicate powder, 20% to 30% magnesium oxide powder, 10% to 20% lanthanum oxide powder, 5% to 10% chromium oxide powder, 4% to 10% nano silicon dioxide powder, and 1% to 5% titanium dioxide powder.

[0007] Furthermore, it is preferred that the laser particle size d50 of the above-mentioned tungsten powder is 0.2μm~0.8μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the molybdenum powder is 1μm~3μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the tantalum powder and the niobium powder is 0.2μm~0.5μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the manganese powder is 4μm~6μm, and the morphology is spherical or nearly spherical.

[0008] The preparation method of the conductive phase powder of the present invention is as follows: tungsten powder, molybdenum powder, tantalum powder, niobium powder and manganese powder are poured into a clean ball mill, and deionized water is poured into the mixture, the mixture is discharged after mixing for 30 to 60 hours, and the mixture is dried at 200 to 220° C., and then the obtained mixed powder is piled in a molybdenum crucible, and the mixture is kept warm in a hydrogen furnace at 1600 to 1700° C. for 10 to 30 hours, and the mixture is cooled to room temperature along with the furnace, crushed, wet-milled in a sand mill for 70 to 100 hours, dried at 100 to 125° C., and passed through a 400-mesh sample sieve.

[0009] Furthermore, it is preferred that the laser particle size d50 of the inorganic non-metallic powder is 0.2 μm to 2 μm.

[0010] The preparation method of the inorganic non-metallic powder of the present invention is as follows: calcium silicate powder, magnesium oxide powder, lanthanum oxide powder, chromium trioxide powder, nano silicon dioxide powder and titanium dioxide powder are poured into a clean ball mill, and deionized water is poured into the mixture, the mixture is mixed for 5 to 10 hours and then discharged, and dried at 100 to 150 DEG C, and then the obtained mixed powder is piled in a corundum crucible, kept warm in an air furnace at 1000 to 1200 DEG C for 3 to 5 hours, cooled to room temperature along with the furnace, crushed, wet ball milled in a sand mill for 20 to 30 hours, dried at 100 to 125 DEG C, and passed through a 400-mesh sample sieve.

[0011] Furthermore, the mass percentage composition of the above-mentioned organic carrier is preferably: 40% to 50% ethyl carbitol, 30% to 40% ethylene glycol phenyl ether, 2% to 10% butyl benzyl phthalate, 1% to 2% furoic acid, 2% to 3% anise oil, and 5% to 10% nitrocellulose.

[0012] The preparation method of the above-mentioned organic carrier is as follows: first, ethyl carbitol, ethylene glycol phenyl ether and butyl benzyl phthalate are poured into a reaction kettle, furoic acid and anise oil are added in sequence, nitrocellulose is slowly poured into the reaction kettle under stirring, and then the temperature is raised to 65±5°C until the nitrocellulose is dissolved and a transparent solution is formed, heating is stopped, the temperature is lowered to room temperature, and the mixture is barreled for later use.

[0013] The invention discloses a method for preparing a low resistance temperature coefficient resistor paste for an electrical component printed circuit. The method comprises the following steps: adding an organic carrier into a double planetary stirring mixer, sequentially adding a conductive phase powder and an inorganic non-metallic powder while stirring, and stirring for 30 minutes after the raw materials are added; grinding the dispersed paste in a three-roll grinder, and passing the grinder through the grinder 10 times; gradually increasing the roller pressure as the number of grindings increases, testing the viscosity and the paste fineness, discharging the material when the viscosity is between 200 and 300 Pa·S and the fineness is ≤8 μm, filtering the paste on a filter press, using a 300-mesh double-layer stainless steel mesh as the filter screen, and then canning the paste.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The present invention uses nano-silicon dioxide powder, which can improve the thixotropy of the slurry and increase the storage stability of the slurry on the one hand, and can also utilize the low melting point of the nano-silicon dioxide powder to reduce the melting point of the glass system to obtain a denser resistor film layer and better adhesion.

[0016] 2. The present invention uses the alloy formed by the high-temperature solid-phase reaction of tungsten powder, molybdenum powder, tantalum powder, niobium powder and manganese powder in hydrogen as the conductive phase, which effectively reduces the temperature coefficient of the resistor paste, and the resistance temperature coefficient is reduced to (0.05-0.1)×10 -3 / ℃. And the manganese powder in the conductive phase will be oxidized into highly active manganese dioxide and manganese oxide under wet hydrogen sintering conditions. These substances will form chemical bonds with the ceramic matrix and enhance the adhesion between the resistor film and the matrix.

[0017] 3. The present invention adds chromium oxide powder and titanium dioxide powder to the inorganic non-metallic powder. Chromium oxide and titanium dioxide will form chromium corundum and titanium corundum chemical bonds with aluminum oxide at high temperature, which will also enhance the adhesion between the resistor film and the substrate.

[0018] 4. The present invention uses ethyl carbitol, ethylene glycol phenyl ether, butyl benzyl phthalate, furoic acid, anise oil, and nitrocellulose as carriers. Compared with diethylene glycol butyl ether and tributyl citrate as carriers of mixed solvents, the carriers are less volatile at room temperature and have lower odor. The present invention uses nitrocellulose as a thickener and adhesive, which is easier to decompose cleanly during sintering and has a smaller ash content.

[0019] 5. The low temperature coefficient of resistance resistor paste for electrical component printed circuit provided by the present invention has a small temperature coefficient of resistance (TCR = (0.05-0.1) × 10 -3 / ℃); fast heating, high heating power at high temperature; small odor, environmentally friendly; good thixotropy of the slurry, easy to print, no sticking to the mesh, high resolution; the thermal expansion coefficient of the metal layer matches that of the ceramic substrate, and has good thermal shock resistance; the resistor film forms a firm bond with the substrate using glass and chemical bonds, and has high adhesion. DETAILED DESCRIPTION

[0020] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, without departing from the concept of the present invention, several variations and improvements can also be made, which all belong to the protection scope of the present invention.

[0021] The laser particle size d50 of the tungsten powder used in the following examples is 0.2μm~0.8μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the molybdenum powder is 1μm~3μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the tantalum powder and the niobium powder is 0.2μm~0.5μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the manganese powder is 4μm~6μm, and the morphology is spherical or nearly spherical. Example 1

[0022] 1. Preparation of conductive phase powder

[0023] Pour 30g of tungsten powder, 60g of molybdenum powder, 5g of tantalum powder, 3g of niobium powder and 2g of manganese powder into a clean ball mill, and add deionized water. Discharge the materials after mixing for 30 hours and dry them at 200°C. Pile the mixed powder in a molybdenum crucible and keep it in a 1650°C hydrogen furnace for 10 hours. Cool it to room temperature with the furnace, break it, wet-mill it with a sand mill for 70 hours, dry it at 125°C, and pass it through a 400-mesh sieve to obtain a conductive phase powder.

[0024] 2. Preparation of inorganic non-metallic powder

[0025] Pour 50g of calcium silicate powder, 20g of magnesium oxide powder, 10g of lanthanum oxide powder, 5g of chromium oxide powder, 10g of nano-silicon dioxide powder and 5g of titanium dioxide powder into a clean ball mill, and add deionized water, mix for 5 hours, discharge the materials, and dry them at 150°C. Then, pile the obtained mixed powder in a corundum crucible, keep it in a 1200°C air furnace for 5 hours, cool it to room temperature with the furnace, break it, wet-ball mill it with a sand mill for 30 hours, dry it at 125°C, and pass it through a 400-mesh sample sieve to obtain an inorganic non-metallic powder with a laser particle size d50 of 0.2μm to 2μm.

[0026] 3. Preparation of organic carrier

[0027] First, pour 45g of ethyl carbitol, 40g of ethylene glycol phenyl ether and 2g of butyl benzyl phthalate into the reactor, add 1g of furoic acid and 2g of fennel oil in turn, slowly pour in 10g of nitrocellulose under stirring, then raise the temperature to 65°C until the nitrocellulose is dissolved to form a transparent solution, stop heating, cool to room temperature, obtain the organic carrier, and put it into a barrel for later use.

[0028] 4. Preparation of resistor paste

[0029] Add 15g of organic carrier into a double planetary stirring mixer, and add 75g of conductive phase powder and 10g of inorganic non-metallic powder in sequence while stirring. Stir for 30 minutes after the raw materials are added; grind the dispersed slurry on a three-roll grinder and pass the knife 10 times; as the number of grindings increases, gradually increase the roller pressure, test the viscosity and slurry fineness, and discharge the material when the viscosity is 200-300Pa·S and the fineness is ≤8μm. Filter the slurry on a filter press, using a 300-mesh double-layer stainless steel mesh to obtain a resistor slurry, which is then canned.

[0030] The properties of the obtained resistor paste are as follows: viscosity 220Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh) 60μm; sintered film thickness 31μm; square resistance 450mΩ / □; temperature coefficient of resistance TCR = 0.08×10 -3 / ℃; thermal shock resistance ≥700℃; solder point tensile force ≥10kg. Example 2

[0031] 1. Preparation of conductive phase powder

[0032] Pour 35g of tungsten powder, 55g of molybdenum powder, 5g of tantalum powder, 3g of niobium powder and 2g of manganese powder into a clean ball mill, and add deionized water. Discharge the materials after mixing for 30 hours and dry them at 200°C. Pile the mixed powder in a molybdenum crucible and keep it in a 1600°C hydrogen furnace for 10 hours. Cool it to room temperature with the furnace, break it, wet-ball mill it with a sand mill for 80 hours, dry it at 125°C, and pass it through a 400-mesh sieve to obtain a conductive phase powder.

[0033] 2. Preparation of inorganic non-metallic powder

[0034] This step is the same as step 2 of Example 1, and an inorganic non-metallic powder with a laser particle size d50 of 0.2 μm to 2 μm is obtained.

[0035] 3. Preparation of organic carrier

[0036] This step is the same as step 3 of Example 1, and the organic carrier is obtained and bucketed for later use.

[0037] 4. Preparation of resistor paste

[0038] Add 15g of organic carrier into a double planetary stirring mixer, and add 80g of conductive phase powder and 5g of inorganic non-metallic powder in sequence while stirring. Stir for 30 minutes after the raw materials are added; grind the dispersed slurry on a three-roll grinder and pass the knife 10 times; as the number of grindings increases, gradually increase the roller pressure, test the viscosity and slurry fineness, and discharge the material when the viscosity is 200-300Pa·S and the fineness is ≤8μm. Filter the slurry on a filter press, using a 300-mesh double-layer stainless steel mesh to obtain a resistor slurry, which is then canned.

[0039] The properties of the obtained resistor paste are as follows: viscosity 200Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh) 64μm; sintered film thickness 32μm; square resistance 420mΩ / □; temperature coefficient of resistance TCR = 0.09×10 -3 / ℃; thermal shock resistance ≥700℃; solder point tensile force ≥10kg. Example 3

[0040] 1. Preparation of conductive phase powder

[0041] Pour 40g of tungsten powder, 50g of molybdenum powder, 5g of tantalum powder, 3g of niobium powder and 2g of manganese powder into a clean ball mill, and add deionized water. Discharge the materials after mixing for 30 hours and dry them at 200°C. Pile the mixed powder in a molybdenum crucible and keep it in a 1600°C hydrogen furnace for 10 hours. Cool it to room temperature with the furnace, break it, wet-mill it with a sand mill for 80 hours, dry it at 125°C, and pass it through a 400-mesh sieve to obtain a conductive phase powder.

[0042] 2. Preparation of inorganic non-metallic powder

[0043] This step is the same as step 2 of Example 1, and an inorganic non-metallic powder with a laser particle size d50 of 0.2 μm to 2 μm is obtained.

[0044] 3. Preparation of organic carrier

[0045] This step is the same as step 3 of Example 1, and the organic carrier is obtained and bucketed for later use.

[0046] 4. Preparation of resistor paste

[0047] This step is the same as step 4 of Example 2, to obtain resistor paste, which is then canned.

[0048] The properties of the resistor paste are as follows: viscosity 230Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh) 56μm; sintered film thickness 28μm; square 410mΩ / □; temperature coefficient of resistance TCR = 0.08×10 -3 / ℃; thermal shock resistance ≥700℃; solder point tensile force ≥10kg. Example 4

[0049] 1. Preparation of conductive phase powder

[0050] This step is the same as step 1 of Example 1 to obtain conductive phase powder.

[0051] 2. Preparation of inorganic non-metallic powder

[0052] This step is the same as step 2 of Example 1, and an inorganic non-metallic powder with a laser particle size d50 of 0.2 μm to 2 μm is obtained.

[0053] 3. Preparation of organic carrier

[0054] First, pour 45g of ethyl carbitol, 40g of ethylene glycol phenyl ether and 2g of butyl benzyl phthalate into the reactor, add 2g of furoic acid and 2g of fennel oil in turn, slowly pour in 9g of nitrocellulose under stirring, then raise the temperature to 65°C until the nitrocellulose is dissolved to form a transparent solution, stop heating, cool to room temperature, obtain the organic carrier, and put it into a barrel for later use.

[0055] 4. Preparation of resistor paste

[0056] Add 10g of organic carrier into a double planetary stirring mixer, and add 80g of conductive phase powder and 10g of inorganic non-metallic powder in sequence while stirring. Stir for 30 minutes after the raw materials are added; grind the dispersed slurry on a three-roll grinder and pass the knife 10 times; as the number of grindings increases, gradually increase the roller pressure, test the viscosity and slurry fineness, and discharge the material when the viscosity is 200-300Pa·S and the fineness is ≤8μm. Filter the slurry on a filter press, using a 300-mesh double-layer stainless steel mesh to obtain a resistor slurry, which is then canned.

[0057] The properties of the obtained resistor paste are as follows: viscosity 220Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh) 62μm; sintered film thickness 30μm; square resistance 450mΩ / □; temperature coefficient of resistance TCR = 0.06×10 -3 / ℃; thermal shock resistance ≥700℃; solder point tensile force ≥10kg. Example 5

[0058] 1. Preparation of conductive phase powder

[0059] Pour 35g of tungsten powder, 55g of molybdenum powder, 5g of tantalum powder, 3g of niobium powder and 2g of manganese powder into a clean ball mill, and add deionized water. Discharge the materials after mixing for 30 hours and dry them at 200°C. Pile the mixed powder in a molybdenum crucible and keep it in a 1650°C hydrogen furnace for 10 hours. Cool it to room temperature with the furnace, break it, wet-mill it with a sand mill for 70 hours, dry it at 125°C, and pass it through a 400-mesh sieve to obtain a conductive phase powder.

[0060] 2. Preparation of inorganic non-metallic powder

[0061] This step is the same as step 2 of Example 1, and an inorganic non-metallic powder with a laser particle size d50 of 0.2 μm to 2 μm is obtained.

[0062] 3. Preparation of organic carrier

[0063] This step is the same as step 3 of Example 4, and the organic carrier is obtained and bucketed for later use.

[0064] 4. Preparation of resistor paste

[0065] Add 12g of organic carrier into a double planetary stirring mixer, and add 80g of conductive phase powder and 8g of inorganic non-metallic powder in sequence while stirring. Stir for 30 minutes after the raw materials are added; grind the dispersed slurry on a three-roll grinder and pass the knife 10 times; as the number of grindings increases, gradually increase the roller pressure, test the viscosity and slurry fineness, and discharge the material when the viscosity is 200-300Pa·S and the fineness is ≤8μm. Filter the slurry on a filter press, using a 300-mesh double-layer stainless steel mesh to obtain a resistor slurry, which is then canned.

[0066] The properties of the obtained resistor paste are as follows: viscosity 210Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh) 60μm; sintered film thickness 32μm; square resistance 500mΩ / □; temperature coefficient of resistance TCR = 0.07×10 -3 / ℃; thermal shock resistance ≥700℃; solder point tensile force ≥10kg.

[0067] In order to better understand the effects of tungsten powder, molybdenum powder, tantalum powder, niobium powder, manganese powder, chromium trioxide powder and titanium dioxide powder on the performance of resistor paste, the following comparative examples are made taking Example 1 as an example:

[0068] Comparative Example 1

[0069] Add 15g of organic carrier (prepared by the same method as in step 3 of Example 1) into a disperser, and add 13g of inorganic non-metallic powder (prepared by the same method as in step 2 of Example 1) and 72g of conductive phase powder (prepared by 2g of manganese powder and 70g of tungsten powder according to the preparation method of step 1 of Example 1) in sequence while stirring. After the raw materials are added, stir for 30 minutes; grind the dispersed slurry on a three-roll grinder, and gradually increase the pressure of the slow roll and the middle roll as the number of grindings increases, test the viscosity and slurry fineness, and discharge the material when the viscosity is 300±50Pa·S and the fineness is ≤8μm. Filter the slurry on a vacuum feeder, and use a 250-mesh double-layer stainless steel mesh to obtain a resistor slurry.

[0070] The properties of the obtained resistor paste are as follows: viscosity 300Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh): 60μm; sintered film thickness 31μm; square resistance 460mΩ / □; temperature coefficient of resistance TCR = 4.5×10 -3 / ℃; tension ≥10kg.

[0071] Comparative Example 2

[0072] Add 15g of organic carrier (prepared in the same way as step 3 of Example 1) into a disperser, and add 14g of inorganic non-metallic powder (prepared by 5g of calcium silicate powder and 9g of nano silicon dioxide powder according to the preparation method of step 2 of Example 1) and 71g of conductive phase powder (prepared in the same way as step 1 of Example 1) in sequence while stirring. After the raw materials are added, stir for 30min. Grind the dispersed slurry on a three-roll grinder. As the number of grindings increases, gradually increase the pressure of the slow roll and the middle roll, test the viscosity and slurry fineness, and discharge the material when the viscosity is 300±50Pa·S and the fineness is ≤8μm. Filter the slurry on a vacuum feeder, and use a 250-mesh double-layer stainless steel mesh to obtain a resistor slurry.

[0073] The properties of the obtained resistor paste are as follows: viscosity 320Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh) 64μm; sintered film thickness 33μm; square resistance 600mΩ / □; temperature coefficient of resistance TCR = 0.06×10 -3 / ℃; tension: 2.8kg.

[0074] Comparative Example 3

[0075] Add 15 g of organic carrier (preparation method is the same as step 3 of Example 1) into a disperser, and while stirring, add 15 g of inorganic non-metallic powder (preparation method is the same as step 2 of Example 1) and 70 g of conductive phase powder (the ingredients are the same as in Example 1, directly added without pre-synthesizing the alloy by high-temperature solid-phase reaction), and stir for 30 minutes after the raw materials are added; grind the dispersed slurry on a three-roll grinder, and gradually increase the pressure of the slow roll and the middle roll as the number of grindings increases, test the viscosity and slurry fineness, and discharge the material when the viscosity is 300±50 Pa·S and the fineness is ≤8μm, and filter the slurry on a vacuum feeder, using a 250-mesh double-layer stainless steel mesh to obtain a resistor slurry.

[0076] The properties of the obtained resistor paste are as follows: viscosity 300Pa·S; fineness ≤8μm; printing thickness (300 mesh stainless steel mesh) 61μm; sintered film thickness 30.2μm; square resistance 450mΩ / □; temperature coefficient of resistance TCR = 1.2×10 -3 / ℃; tension ≥10kg.

[0077] Based on the test results of Example 1 and Comparative Examples 1 to 3, it can be seen that the conductive phase powder prepared without adding molybdenum powder, tantalum powder, and niobium powder in Comparative Example 1 has a resistance temperature coefficient of the resistor paste that is significantly more than 6 times greater than that in Example 1, indicating that the present invention uses the alloy formed by high-temperature solid-phase reaction of tungsten powder, molybdenum powder, tantalum powder, niobium powder, and manganese powder as the conductive phase, which can effectively reduce the temperature coefficient of the resistor paste. In Comparative Example 2, the inorganic non-metallic powder only contains calcium silicate powder and nano-silicon dioxide powder, and the resistance temperature coefficient of the resistor paste is basically unchanged compared with Example 1, but its pulling force is greatly reduced to only 2.8 kg, which does not reach the predetermined adhesion. The inventors further found that if the inorganic non-metallic powder contains only calcium silicate powder, magnesium oxide powder, and lanthanum oxide powder, the tensile force of the resistor paste is only 1.5kg; if the inorganic non-metallic powder contains only calcium silicate powder, magnesium oxide powder, lanthanum oxide powder, and nano-silicon dioxide powder, and does not contain chromium trioxide powder and titanium dioxide powder, the tensile force of the resistor paste can reach 5.2kg; if the inorganic non-metallic powder contains calcium silicate powder, magnesium oxide powder, lanthanum oxide powder, nano-silicon dioxide powder, chromium trioxide powder, and titanium dioxide powder at the same time, the tensile force of the resistor paste can reach ≥10kg. Compared with the direct mixing of tungsten powder, molybdenum powder, tantalum powder, niobium powder and manganese powder as the conductive phase in Comparative Example 3, the high-temperature solid phase reaction of tungsten powder, molybdenum powder, tantalum powder, niobium powder and manganese powder in Example 1 forms an alloy powder as the conductive phase, and the resistance temperature coefficient of the resistor paste is smaller, which shows that it is necessary to pre-synthesize the alloy powder.

Claims

1. A low resistance temperature coefficient resistor paste for printed circuits of electrical components, characterized in that: The resistor paste is composed of the following raw materials in percentage by weight: 70% to 80% conductive phase powder, 5% to 15% inorganic non-metallic powder, and 10% to 15% organic carrier; The conductive phase powder is an alloy powder prepared by a high temperature solid phase method from the following raw materials in mass percentage: 30% to 40% tungsten powder, 40% to 60% molybdenum powder, 4% to 16% tantalum powder, 1% to 3% niobium powder, and 1% to 2% manganese powder; The inorganic non-metallic powder is prepared by calcining the following raw materials in mass percentage in an air atmosphere: 50% to 60% calcium silicate powder, 20% to 30% magnesium oxide powder, 10% to 20% lanthanum oxide powder, 5% to 10% chromium oxide powder, 4% to 10% nano silicon dioxide powder, and 1% to 5% titanium dioxide powder.

2. The low resistance temperature coefficient resistor paste for electrical component printed circuit according to claim 1, characterized in that: The laser particle size d50 of the tungsten powder is 0.2μm to 0.8μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the molybdenum powder is 1μm to 3μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the tantalum powder and niobium powder is 0.2μm to 0.5μm, and the morphology is spherical or nearly spherical; the laser particle size d50 of the manganese powder is 4μm to 6μm, and the morphology is spherical or nearly spherical.

3. The low temperature coefficient of resistance resistor paste for electrical component printed circuit according to claim 1, characterized in that: The laser particle size d50 of the inorganic non-metallic powder is 0.2 μm to 2 μm.

4. The low resistance temperature coefficient resistor paste for electrical component printed circuit according to claim 1, characterized in that: The conductive phase powder is prepared by the following method: pouring tungsten powder, molybdenum powder, tantalum powder, niobium powder and manganese powder into a clean ball mill jar, and pouring deionized water into it, discharging the materials after mixing for 30 to 60 hours, drying at 200 to 220° C., then piling the obtained mixed powder in a molybdenum crucible, keeping it warm in a hydrogen furnace at 1600 to 1700° C. for 10 to 30 hours, cooling it to room temperature with the furnace, crushing it, wet ball milling it with a sand mill for 70 to 100 hours, drying it at 100 to 125° C., and passing it through a 400-mesh sample sieve.

5. The low resistance temperature coefficient resistor paste for electrical component printed circuit according to claim 1, characterized in that: The inorganic non-metallic powder is prepared by the following method: calcium silicate powder, magnesium oxide powder, lanthanum oxide powder, chromium trioxide powder, nano silicon dioxide powder and titanium dioxide powder are poured into a clean ball mill, and deionized water is poured into the mixture, the mixture is mixed for 5 to 10 hours and then discharged, and dried at 100 to 150° C., and then the obtained mixed powder is piled in a corundum crucible, kept warm in an air furnace at 1000 to 1200° C. for 3 to 5 hours, cooled to room temperature along with the furnace, crushed, wet ball milled in a sand mill for 20 to 30 hours, dried at 100 to 125° C., and passed through a 400-mesh sample sieve.

6. The low resistance temperature coefficient resistor paste for electrical component printed circuit according to claim 1, characterized in that: The mass percentage composition of the organic carrier is: 40% to 50% ethyl carbitol, 30% to 40% ethylene glycol phenyl ether, 2% to 10% butyl benzyl phthalate, 1% to 2% furoic acid, 2% to 3% anise oil, and 5% to 10% nitrocellulose.

Citation Information

Patent Citations

  • Co-fired high-temperature heating slurry for alumina ceramic heater and preparation method thereof

    CN109734480A

  • A tungsten paste for high-power circuits

    CN112289483B

  • Method for preparing electrical property-controllable zinc oxide (ZnO) piezoresistor material at low temperature

    CN102476949A

  • Tungsten slurry for high-power circuit

    CN112289483A